A rectifier-less ac–dc interface circuit for ambient energy harvesting from low-voltage piezoelectric transducer array - Shareef, Arish (2019)
This paper presents a rectifier-less ac-dc energy harvesting circuit capable of harvesting energy from multiple low-voltage piezoelectric transducers (PETs). Synchronous electric charge extraction technique, with bidirectional switches, is adopted to achieve rectifier-less ac-dc direct conversion. The inductor is engaged only during the voltage peak of the PET output for a short period of time and therefore, a single inductor can be shared by multiple transducers. A split-capacitor charging topology is employed to harvest both positive and negative half-cycle energies, without the use of an input rectifier. In addition, a self-startup function is incorporated to kick-start the system from low input voltages. A prototype has been implemented with off-the-shelf components. Energy harvesting from three PET energy sources with different resonance frequencies is demonstrated. A peak overall power conversion efficiency of 79% is achieved with a system self-startup voltage of 650 mV.